FITOMASA SUBTERRÁNEA Y AÉREA EN PASTOS DE DEHESA - Puerto Martín, A; Puerto, A (Pastos, 1992)
A study has been conducted on the spatial variations undergone by root biomass, aerial phytomass and the root/shoot ratio in grassland communities (dehesa systems). These variations are governed by the prevailing gradients: topographic and the effect of the tree canopy. The greatest biomass, both underground and aerial, and the lowest root/shoot ratio are usually found in the more fertile sites (deposition sector of slope) and shaded áreas (under the crowns of the trees), in contrast to the results of some researchs performed in cultures or at the laboratory. In the case of natural or semi-natural groupings of herba- ceous species in severe environments, the adaptive responses of each species appear to predomínate over any generalized type of response. Key
Keywords: España; fitomasa; Grasslands; influencia del arbolado; ladera; pastos; phytomass; Salamanca; Salamanca (Spain); slope; tree canopy ¡nfluence